Penggunaan Media Film Animasi dalam Meningkatkan Akhlak Anak Usia 5-6 Tahun di RA Al-Barkah Medan Helvetia - Rantika Wulandari; Khadijah Khadijah; Sholihatul Hamidah Daulay (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The idea behind the study project, "Use of Animation Film Media in Improving the Morals of Children Aged 5–6 Years at RA Al-Barkah Medan Helvetia," is that the morals of the participants at RA Al-Barkah are not yet in their best condition. The aims of this research were to: (1) determine the morals of children aged 5 to 6 years at RA Al-Barkah Medan Helvetia; (2) investigate the methods used to use animated films to improve moral development in this age group; and (3) determine whether animated film media can improve the morals of this age group. Planning, implementation, observation and reflection activities are part of the two-cycle Classroom Action Research (PTK) technique used in this research at RA Al-Barkah. Researchers use documentation and observation sheets to determine the improvements that have occurred. The research results show how the films Nussa and Rara raise children's moral standards. The increase in the proportion of children's moral markers in each cycle shows this result. There was an increase in cycle I, namely 6 children (40%) and 9 children (60%) who respectively did not experience development. The proportion of children's moral indicators increased in cycle II, namely 2 children (13.33%) who began to experience development and 13 children (86.66%) who experienced very good development. Therefore, animated films at RA Al-Barkah Medan Helvetia can help children aged five to six years to develop better morals.